Sociodemographic and gestational characteristics of adolescent mothers - Vieira Amaral, Jackeline; Rocha Arrais, Kamilla; Dantas Almeida, Priscilla; Rocha Arrais, Kellícia; Bastos Coelho, Bruno Raphael; Antunes de Araujo Filho, Augusto Cezar (Revista Prevenção de Infecção e Saúde, 2022)
Introduction: The teenage pregnancy has been considered a worldwide health problem for more than four decades due to the biological, psychological, economical, educational and familial consequences. The study aims to analyze the epidemiological profile of teenage pregnancy in a northeastern Brazilian capital. Outline: It is a descriptive, retrospective study, with quantitative approach, performed with secondary data from Department of Informatics of SUS (DATASUS), in the years from 2013 to 2017. Results: A higher record of pregnancy among the teenagers was observed in the age range of 15 to 19 years, with 8 to 11 years of schooling and married. There was a reduction in the number of pregnancies, but with fluctuations between 2013 and 2014. The obstetric-gestational profile revealed that most of the teenagers had attended seven or more prenatal care appointments, had single pregnancy and vaginal delivery. Most of the newborns had adequate weight at birth and low frequency of prematurity, asphyxia at birth (Apgar at 1st and 5th minute between 8 and 10) and of congenital anomalies. Implications: The study enabled the gestational situation of the teenagers to be recognized, contributing to the health care strategies, prevention of teenage pregnancy and mother-baby adequate assistance.